Short-Term and Long-Term Outcomes of Mesh Versus Non-Mesh Repair in Emergency Inguinal Hernia Surgery (مجلة الرازي الطبية, 2026)
Emergency inguinal hernia repair represents a significant surgical challenge due to the urgent nature of presentations, often complicated by incarceration, strangulation, bowel obstruction, and tissue ischemia. These conditions increase morbidity and mortality compared with elective hernia surgery, necessitating prompt diagnosis and immediate intervention. Surgical repair remains the definitive treatment, with techniques broadly categorized into mesh-based (tension-free) and non-mesh (tissue-based) repairs. Non-mesh methods, such as Bassini, Shouldice, and McVay, have historically been used but are associated with tension at the repair site, higher recurrence rates, and prolonged recovery. Mesh-based repairs, particularly tension-free techniques, provide stronger reinforcement, reduce recurrence, and improve functional recovery, though concerns about infection, chronic pain, and foreign body complications persist. Short-term outcomes in emergency settings are influenced by factors such as tissue viability, contamination, patient comorbidities, obesity, and smoking. Mesh placement during contaminated or emergent cases may increase morbidity, although surgical site infection rates do not necessarily rise. Long-term outcomes consistently show that mesh repairs achieve lower recurrence rates and comparable chronic pain levels compared with non-mesh repairs, while tissue-based techniques remain relevant in selected patient populations. Evidence underscores the importance of individualized surgical planning, careful technique selection, and optimization of modifiable risk factors to improve both short- and long-term outcomes. This review highlights current evidence on clinical outcomes following emergency inguinal hernia repair, emphasizing the balance between patient safety, recurrence prevention, and quality of life.